Effect of the MoS2 surface layer on the kinetics of intercalation processes in the NaFe(SO4)2/C composite. (September 2021) - Kokhmetova, Saule; Kan, Tatyana; Malchik, Fyodor; Galeyeva, Alina; Djenizian, Thierry; Kurbatov, Andrey
Abstract: The article deals with the problem of electrochemical conversion of low-conductive materials considering an example of eldfellite-structured NaFe(SO4 )2 . The applying process of electronically-conducting material on NaFe(SO4 )2 surface by means of milling providing multiple contacts with the conductive phase and thus delivering electrons to the active material is given a detailed study. The material which has point contact conductivity (Carbon black) is proposed to replace partially by the layer-structured ones (MoS2 ), thus ensuring full coverage of the active material coating, and, appropriately, wider area of charge delivery to the material's surface. A schematic diagram is proposed of the intercalation process into the active material particles covered with a layer of electron- and ion-conductive additive MoS2 . It follows from the scheme that the extreme dependence found experimentally for such electrochemical parameters as the charge/discharge capacity, CV peak current, diffusion coefficient (in solid phase) and half-wave intercalation potential is associated with the thickness of the applied coating. The detected extremum in the dependence of the de/intercalation parameters on the coating thickness is induced by the potential drop during the charge transfer through the coating phase and is confirmed by a quantitative analysis of the process model. Graphical Abstract: ga1